2016
DOI: 10.1007/s00213-016-4404-9
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal kynurenine exposure in rats: age-dependent changes in NMDA receptor expression and conditioned fear responding

Abstract: Levels of kynurenic acid (KYNA), an endogenous negative modulator of alpha 7 nicotinic acetylcholine (±7nACh) and antagonist at glutamatergic N-methyl-D-aspartate (NMDA) receptors, are elevated in the brain of patients with schizophrenia (SZ). In rats, dietary exposure to KYNA’s immediate precursor kynurenine during the last week of gestation produces neurochemical and cognitive deficits in adulthood that resemble those seen in patients with SZ. The present experiments examined whether prenatal kynurenine expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 83 publications
1
30
0
Order By: Relevance
“…Therefore, it is possible that persistent elevations of KYNA in the PFC during adolescence may elicit enduring GABAergic dysfunction and disrupt the acquisition of inhibitory control that normally emerges in the adult PFC (Caballero et al, 2016). Elevations of KYNA levels during sensitive periods of perinatal development Alexander et al, 2013;Forrest et al, 2013;Liu et al, 2014;Pisar et al, 2014;Pershing et al, 2015Pershing et al, , 2016 or adolescence (Akagbosu et al, 2012;DeAngeli et al, 2014, Pershing et al, 2016 may alter the balance of E-I in the PFC and contribute to the onset of cognitive deficits later in life, as seen in schizophrenia and other major psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is possible that persistent elevations of KYNA in the PFC during adolescence may elicit enduring GABAergic dysfunction and disrupt the acquisition of inhibitory control that normally emerges in the adult PFC (Caballero et al, 2016). Elevations of KYNA levels during sensitive periods of perinatal development Alexander et al, 2013;Forrest et al, 2013;Liu et al, 2014;Pisar et al, 2014;Pershing et al, 2015Pershing et al, , 2016 or adolescence (Akagbosu et al, 2012;DeAngeli et al, 2014, Pershing et al, 2016 may alter the balance of E-I in the PFC and contribute to the onset of cognitive deficits later in life, as seen in schizophrenia and other major psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Of special interest in this context is the abnormal elevation of the tryptophan metabolite kynurenic acid (KYNA) in the PFC of individuals with schizophrenia, a biochemical dysregulation that is not secondary to antipsychotic medication Ceresoli-Borroni et al, 2006;Larsson et al, 2015). Brain KYNA is an astrocyte-derived metabolite that is present in the mammalian CNS at nanomolar concentrations (Moroni et al, 1988;Turski et al, 1988) and negatively modulates ␣7-nicotinic acetylcholine receptor (␣7nAChR) function under physiological conditions (Albuquerque and Schwarcz, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, elevations in KYNA during sensitive periods of late gestation, have also been shown to reduce the gain of GABAergic transmission that occurs post-adolescence in the maturing PFC (Thomases et al, SFN 2014). In line with these neurochemical and electrophysiological effects, acute elevation of KYNA levels in adults, or chronic elevations of KYNA during sensitive periods of development, causes cognitive deficits that resemble those seen in persons with SZ, including diminished cognitive flexibility (Alexander et al, 2012; Alexander et al, 2013; Pershing et al, 2015), trace fear conditioning (Pershing et al, 2016), spatial working memory, and conditioned avoidance tasks (Pocivavsek et al, 2012). …”
Section: 0 Introductionmentioning
confidence: 95%
“…Specifically, kynurenic acid (KYNA) has been involved in brain development 17 and cognitive process 18 since it is the unique endogenous antagonist of NMDA receptor and a negative allosteric modulator of alpha7-nicotinic receptors. It has been suggested that the high KYNA levels found in fetal brain as well as its rapid decline during the postnatal period, are involved in NMDAr modulation, necessary for the normal brain development 19,20 . In this context, it has been shown that the fluctuation in brain KYNA levels can cause impairment in working memory, sensorimotor gating and in the attention process in adult rodents [21][22][23] .Numerous publications have recently demonstrated that both Pb 2+ exposure as well as KYNA levels fluctuation during the pre-and postnatal period, lead to cognitive impairment.…”
mentioning
confidence: 99%